The role of sustainable procurement on risk management in an organisation - Nanyonjo Daisy (Uganda Christian University, 2024)
This study examined the role of sustainable procurement on risk management in Ministry of Finance, Planning and Economic Development. The study was guided by the following objectives: to examine the role of sustainable procurement on compliance risk management in Ministry of Finance, Planning and Economic Development; to examine how sustainable procurement helps on supplier risk management; and to examine relationship between sustainable procurement and operational risk management. The respondents of this study were staff of Ministry of Finance, Planning and Economic Development. The respondents were selected on their basis of having crucial roles they play in sustainable procurement and risk management in Uganda. A total of 50 respondents formed the sample size of the study. The study employed a case study design and adopted a mostly quantitative approach. Questionnaires were used for the purpose of data collection and an interview guide was employed for qualitative data. The response rate was 100% of the targeted sample size. The study therefore provides a crucial insight of the role of sustainable procurement on compliance risk management in MFPED was established that sustainable procurement helps us manage our organization's exposure to legal or regulatory sanctions, helps us to ensure business continuity and in monitoring changes in regulatory environment to ensure that our organization is well informed and up-to-date on the requirements, as well as enhancing our ability to deal with financial loss in our organization. The study concluded that the ways in which sustainable procurement helps in supplier risk management were that sustainable purchasing practices enhances our supplier risk management, enhances our organization’s ability to significant control costs that come as a result of disruptions and assists us in avoid economic damage. This is coupled with aiding us in managing operational damage and helping in controlling reputational damage. The study concluded that the relationship between sustainable procurement and operational risk management was established that sustainable procurement assists our capacity to avoid possible failures in operations related directly to financial risk, helping organization’s ability to handle eventualities from management and procedures and enhancing the organization’s ability to handle eventualities from risks associated with information systems and augmenting the organization’s ability to handle eventualities from people and systems.